2014
DOI: 10.1039/c4tc01998a
|View full text |Cite
|
Sign up to set email alerts
|

Polymer composites of boron nitride nanotubes and nanosheets

Abstract: A comprehensive review of polymer composites of BN nanotubes and nanosheets with distinguished properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
134
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(138 citation statements)
references
References 167 publications
(198 reference statements)
3
134
0
1
Order By: Relevance
“…The copper cylinders assembly (sandwiching the TIM composite adhesive) was placed between the heating and cooling stages. After achieving steady state conditions, temperatures were noted which were used to calculate thermal contact resistances according to equations reported in [17]. The total thermal contact resistance of the coating is proportional to its bond line thickness.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The copper cylinders assembly (sandwiching the TIM composite adhesive) was placed between the heating and cooling stages. After achieving steady state conditions, temperatures were noted which were used to calculate thermal contact resistances according to equations reported in [17]. The total thermal contact resistance of the coating is proportional to its bond line thickness.…”
Section: Methodsmentioning
confidence: 99%
“…Like carbon nanomaterials, BN can also have several nanostructures which make it an interesting filler material for polymer composites [17]. Few research articles report thermal conductivity of hybrid composites produced with BN and carbon nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…[178,179]. Huang et al [42,43] reported an ideal dielectric thermally conductive epoxy nanocomposite using POSS-functionalized BNNTs as fillers (Fig.…”
Section: Bn Bnns and Bnntsmentioning
confidence: 99%
“…[3][4][5] Therefore, there is an urgent need to develop a new strategy to prepare desired materials with high thermal conductivity. Inorganic llers, such as aluminum nitride, 6,7 alumina, 8,9 or boron nitride, [1][2][3][4][5][10][11][12][13][14][15][16][17] have been added to polymer matrices to improve the thermal performance because of their high thermal conductivity and electric insulation. Hexagonal boron nitride (hBN), also called white graphite, has attracted much attention due to its high thermal conductivity, relatively lower density, and a large band gap (nearly 5.9 eV), which make it suitable for applications in thermally conductive and insulating composites.…”
Section: Introductionmentioning
confidence: 99%